2021
DOI: 10.1029/2021gl092511
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy and Wind Driven Changes in Subantarctic Mode Water During 2004–2019

Abstract: The formation and transport of the Subantarctic Mode Water (SAMW) are part of the upper branch of the global meridional overturning circulation (Hanawa & Talley, 2001;McCartney, 1997). The SAMW accounted for more than half of the heat gain in the upper 2,000 m of the Southern Ocean during (Roemmich et al., 2015 and contributes significantly to the global ocean heat capacity (Morrison et al., 2016;Rathore et al., 2020). It is also the largest contributor to the uptake and storage of anthropogenic carbon dioxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 58 publications
0
18
2
Order By: Relevance
“…In this study, although both Argo observations and CMIP6 models do not have sufficient resolution to identify eddies, they are capable of capturing the characteristics of SEISAMW and are comparable overall. Meanwhile, the long-term trend of SEISAMW simulated by CMIP6 models is similar to that of SAMW simulated by an eddy-resolving ocean model, which also has become warmer, fresher, lighter, and weaker in recent decades (Xu et al, 2021). In addition, there may be ensemble variability within a single CMIP model, because we used one ensemble member "r1i1p1f1" for CMIP6 models.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In this study, although both Argo observations and CMIP6 models do not have sufficient resolution to identify eddies, they are capable of capturing the characteristics of SEISAMW and are comparable overall. Meanwhile, the long-term trend of SEISAMW simulated by CMIP6 models is similar to that of SAMW simulated by an eddy-resolving ocean model, which also has become warmer, fresher, lighter, and weaker in recent decades (Xu et al, 2021). In addition, there may be ensemble variability within a single CMIP model, because we used one ensemble member "r1i1p1f1" for CMIP6 models.…”
Section: Discussionmentioning
confidence: 81%
“…It is interesting that the SAMWs also show volume loss in the previous CMIP3 and CMIP5 coupled models under anthropogenic forcing (Downes et al, 2010;Sallée et al, 2013b;Xia et al, 2021). The mechanism is explained primarily by the reduction of buoyancy gain in the SAMW formation region, while the increasing zonal wind stress induced Ekman transport enhancement plays the secondary role (Downes et al, 2009;Sallée et al, 2010aSallée et al, , 2010b2013a;Xia et al, 2021;Xu et al, 2021). In addition, the SEISAMWs show lighter tendency of potential density in most of the analyzed CMIP6 coupled models (Figure 14).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Xu et al. (2021) found that the SAMW is weakening during 2004–2019 based on the SAMW core layer (PV minimum layer) variation, which is mainly influenced by surface buoyancy gain due to climate warming. A recent study also indicated that the SAMW seasonal variations are governed by buoyancy flux changes (Li et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al (2020) indicated that the Indian Ocean SAMW volume changes are controlled by surface forcing, which is related to the Mascarene High. Some earlier studies considered SAMW in the Indian, Pacific and Atlantic Oceans as a whole when discussing the SAMW variations (Gao et al, 2018;Li et al, 2021; S. R. Rintoul & England, 2002;Xu et al, 2021) and summarized the overall characteristics of the SAMW variations. However, previous study found that the characteristics of SAMW properties are different in each ocean: SAMW is cooler and thicker in the Pacific and eastern Indian Oceans but warmer and thinner in the Atlantic and western Indian Oceans (Herraiz-Borreguero & Rintoul., 2011;McCartney, 1982).…”
mentioning
confidence: 99%